A tailored training programme for South African physiotherapists on the use of evidence-based clinical practice guidelines when treating patients with acute and sub-acute low back pain - Stander, Jessica (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.